Case Report: Exacerbation of Relapses Following mRNA COVID-19 Vaccination in Multiple Sclerosis: A Case Series - Quintanilla-Bordás, Carlos; Gascón-Gimenez, Francisco; Alcalá, Carmen; Payá, María; Mallada, Javier; Silla, Raquel; Carratalà-Boscà, Sara; Gasque-Rubio, Raquel; Castillo, Jessica; Casanova, Bonaventura (Frontiers in Neurology, 2022)
Introduction: mRNA COVID-19 vaccination has been widely used to arrest the spread of the SARS-CoV-2 pandemic. Rare autoimmune events, including relapses in patients with multiple sclerosis (MS) have been reported. We describe a series of four patients that started with symptoms of acute demyelination of the central nervous system due to non-recognized multiple sclerosis (MS), received mRNA COVID-19 vaccination and developed afterwards a catastrophic relapse. Patient and methods: A detailed description of each case, including MRI studies, serum light neurofilament levels, and cerebrospinal fluid cytokine profile is provided. Case description: All patients showed typical MRI features of highly active MS and fulfilled McDonald criteria at time of presentation. All presented high serum light-neurofilament levels and oligoclonal G bands restricted to the cerebrospinal fluid. Higher levels of interleukin-6 (IL-6) in the CSF were present in the more severe cases. Discussion: We describe exacerbation of relapses after mRNA COVID-19 vaccination. We hypothesize RNA sensors such Toll-like receptor 7 may be activated and contribute to amplify the inflammatory response during a relapse. Conclusion: We suggest performing fast diagnostic procedures and prompt treatment in patients with acute neurological symptoms before receiving vaccination. Despite the biological rationale for this phenomenon, further study and pharmacovigilance is warranted to confirm causality